Immunogenicity and Safety of the COVID-19 Vaccines Compared With Control in Healthy Adults: A Qualitative and Systematic Review - Lau, Oscar; Vadlamudi, Nirma Khatri (Value in health, 2022)
Emergence of severe acute respiratory syndrome coronavirus 2 infections and the resultant disease, COVID-19 led the world into 238 million cases and 4.8 million deaths over the first 22 months of the pandemic. While numerous vaccines have been developed to combat this pandemic, limited literature is available regarding the comparison of these vaccines. This study aims to systematically review and evaluate the immunogenicity and safety of COVID-19 vaccines compared with control arms in the healthy adult population. A literature search was conducted in PubMed, MEDLINE, Embase, and Cochrane up to July 4, 2021. Randomized controlled trials assessing the immunogenicity of any dose of COVID-19 vaccine in adults by anti–severe acute respiratory syndrome coronavirus 2 immunoglobulin G antibodies geometric mean titers (GMTs) and neutralizing antibodies GMT response at 28 days postimmunization compared with the control groups in the healthy adults were considered for inclusion. Groups at day 28 with the highest GMT were further examined for their adverse events. Of the 341 citations retrieved, 19 were included. This covered a total of 16 vaccines involving 8342 subjects aged between 30.8 and 69.7 years, comprising 52.13% females. All studies reported GMT at or close to 28 days postvaccination compared with placebo and comparator, and 13 of 19 studies reported seroconversion rates. While 15 of 16 vaccines reported adverse events that ranged from mild to severe, 1 of 16 (AD26.COV2.S) noted 1 case of a vaccine-related serious adverse event—high fever 6 hours after vaccination. Local reactions (such as redness, pain, and swelling) and systematic reactions (such as fatigue, fever, and headache) were commonly noted. Safety between vaccines was similar; however, higher rates of severe adverse events were noted in Ad5-vectored COVID-19, AD26.COV2.S, ChAdOx nCoV-19, and mRNA-1273. No all-cause mortality was documented in any vaccines. All 16 vaccines elicited an immune response substantially higher than the control groups while maintaining tolerable safety profiles. •COVID-19 vaccines are currently used on the basis of immunogenicity and safety profiles data. This study provides a comprehensive and up-to-date qualitative review of the COVID-19 vaccine data in the literature.•Adverse events and immunogenicity profiles in COVID-19 vaccines were similar between younger (18-59 years old) and older (60 years and older) adults.